Monitoring raspberry cane midge (Resseliella theobaldi) on the basis of temperature data - Sipos, Kitti; Pénzes, Béla (Acta Agraria Debreceniensis, 2010)
The ’midge blight’, in which the raspberry cane midge (Resseliella theobaldi) has an important role, is the greatest problem in the raspberry protection. The basis of the chemical protection against raspberry cane midge is the prediction of adult midge emergence. Before the application of sex pheromone traps developed for the investigation of flight pattern, the usage of the accumulated temperature was attempted for the prediction of egg laying, but these temperatures are different in each country. The aim of this paper is to give information on the time of raspberry cane midge emergence and flight pattern by using sex pheromone traps and accumulated temperature calculation.